Upaya Pendampingan Masyarakat Dalam Mencegah Terjadinya Stunting Di Desa Maccinibaji Kecamatan Bajeng Kabupaten Gowa - Hasrianti,; Rasyid Masri,; Nur Laelah Abbas, (Jurnal Berita Sosial, 2024)
This research discusses Community Assistance Efforts to Prevent Stunting in Maccinibaji Village, Bajeng District, Gowa Regency. The main problems in this research are: 1). What is the condition of families at risk of stunting in Maccinibaji Village? 2). How are community assistance efforts to prevent stunting in Maccinibaji Village? The type of research used is descriptive qualitative research. The data sources for this research are community assistants, village midwives, village government and the Maccinibaji Village community, especially pregnant women and mothers with toddlers. Furthermore, the data collection method is carried out through observation, interviews and documentation. Data analysis is used by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research show that: (1) The condition of families at risk of stunting in Maccinibaji Village is a family that contains pregnant mothers, prospective brides and grooms who have Chronic Energy Deficiency (CED), which we can know by measuring the circumference of their upper arms <23.5 cm which is caused by Economic factors and parental knowledge about healthy and proper nutrition for their children are lacking among people who are at risk of stunting. (2) Efforts to assist the community in preventing stunting in Maccinibaji Village include: This awareness stage aims to prevent stunting by providing education about stunting. The independence stage includes preparing oneself to become aware of stunting prevention. This evaluation stage aims to review what has been done to address stunting prevention. The implication of this research is that community assistants together with midwives and the village government will further improve their performance in assisting families at risk of stunting and stunted children. As well as assistance to pregnant women who (Chronic Energy Deficiency) KEK is expected to be even more optimal. And for the people of Maccinibaji Village, they will be wiser in maintaining a healthy lifestyle and parenting their children so that they do not experience stunting.